Optimal parallel randomized renaming - Farach, Martin; Muthukrishnan, S. (Information processing letters, 1997)
We consider the Renaming Problem, a basic processing step in string algorithms, for which we give a simultaneously work and time optimal Las Vegas type PRAM algorithm. The Renaming Problem is closely related to the Multiset Sorting Problem.